Effect of individually controlled personalized ventilation on cross-contamination due to respiratory activities. (May 2021) - Katramiz, Elvire; Ghaddar, Nesreen; Ghali, Kamel; Al-Assaad, Douaa; Ghani, Saud
Abstract: While personalized ventilation (PV) has been integrated to enhance inhaled air quality, some studies showed that it can contribute to contaminants' transport indoors. This work investigates the effect of the individual preferences of PV users on potential cross-contamination in an office. Two occupants were using PV, sitting either face to face or back to face (i.e. in tandem). One of the occupants was infecting the office space through two respiratory activities: coughing and breathing. The PV flowrate control ranged between 0 and 13 l/s, ensuring thermal comfort. A 3-D computational fluid dynamics model was developed and experimentally validated in a climatic chamber equipped with one thermal manikin representing the infected person and a heated dummy representing the healthy person. The cross-contamination was assessed using the inhaled intake fraction ( i F ) index, which is the ratio of the contaminants' mass inhaled by the healthy person to that exhaled by the infected person. It was found that minimal exposure levels were reached when the infected person used low PV (in the range of 0–4 l/s) for the tandem seating and high PV(in the range of 9–13 l/s) for the face-to-face seating. Furthermore, the average iF for face-to-face seating was 31% lower than that of tandem seating for coughing and 86% for breathing for all possible PV ventilation cases. Graphical abstract: Image 1 Highlights: Effect of individual flow control of personalized ventilation (PV) on cross-contamination. Tandem and facing seating with two contaminant sources (breathing, coughing) are studied. A CFD model was developed to assess exposure via the inhaled intake fraction iF index. Low exposure is ensured for healthy person at PVi  < 4 l/s in tandem and PVi  > 9 l/s in facing positions. Average iF of facing seating was lower than tandem seating by 31% (coughing) and 86% (breathing).